2021
DOI: 10.5194/esd-12-763-2021
|View full text |Cite
|
Sign up to set email alerts
|

Bookkeeping estimates of the net land-use change flux – a sensitivity study with the CMIP6 land-use dataset

Abstract: Abstract. The carbon flux due to land-use and land-cover change (net LULCC flux) historically contributed to a large fraction of anthropogenic carbon emissions while at the same time being associated with large uncertainties. This study aims to compare the contribution of several sensitivities underlying the net LULCC flux by assessing their relative importance in a bookkeeping model (Bookkeeping of Land Use Emissions, BLUE) based on a LULCC dataset including uncertainty estimates (the Land-Use Harmonization 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…This includes how the number of PFTs vary between the land surface schemes and whether or not they include land management. The background information from LUH2, which prescribes the locations and timing of historical land use, also has demonstrated uncertainties and limitations (Hartung et al 2021;Prestele et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This includes how the number of PFTs vary between the land surface schemes and whether or not they include land management. The background information from LUH2, which prescribes the locations and timing of historical land use, also has demonstrated uncertainties and limitations (Hartung et al 2021;Prestele et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A large contribution of uncertainty can be expected from various input datasets. Apparent uncertainties arise from the land-use forcing data (Gasser et al, 2020;Hartung et al, 2021;Ganzenmüller et al, 2022), the equilibrium carbon densities of soil and vegetation and allocation of material upon a land-use transition (Bastos et al, 2021), and the response curves built to reflect carbon pool decay and regrowth after land-use transitions. Furthermore, studies have shown that different accounting schemes (Hansis et al, 2015) and initialization settings at the start of the simulations (Hartung et al, 2021)…”
Section: Bookkeeping Modelsmentioning
confidence: 99%
“…The estimates of the land use flux vary widely across models related to differences in (i) underlying land use reconstructions, (ii) the degree of implementation of land use practices, (iii) definitions of the land use flux, and (iv) modeling parameterizations and process representation (Pongratz et al, 2018 ): (i) The source and implementation of information on changes in agricultural areas and forest management differ across studies (Friedlingstein et al, 2022 ) and substantially influence land use flux estimates (Gasser et al, 2020 ), as does uncertainty in the land use reconstructions themselves (Hartung et al, 2021 ). (ii) Land use practices (e.g., drainage, shifting cultivation, wood harvest) are implemented by the models to different extents (Arneth et al, 2017 ) and with varying complexity (Pongratz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%